2005
DOI: 10.1002/pd.1262
|View full text |Cite
|
Sign up to set email alerts
|

Discordant growth in twins

Abstract: Discordant growth in twins contributes significantly to rates of perinatal morbidity and mortality. These rates vary according to chorionicity, timing of onset and severity. We have reviewed English language literature in Medline since 1980. It is clear that diagnosis of discordant growth has improved due to the use of serial ultrasound examination. Following the detection of differences in fetal size, diagnosis is facilitated by umbilical artery and fetal Doppler studies. Management options vary according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…The occurrence of any diseases in twins raises the issue of phenotypic concordance or discordance and the subsequent issue of managing pregnancy, patients, parents and decision making events [6]. Risk assessment for the apparently healthy twin, genetic counselling and parental psychological assistance must be part of the clinical follow-up.…”
Section: Emerging Issues In Twinsmentioning
confidence: 99%
“…The occurrence of any diseases in twins raises the issue of phenotypic concordance or discordance and the subsequent issue of managing pregnancy, patients, parents and decision making events [6]. Risk assessment for the apparently healthy twin, genetic counselling and parental psychological assistance must be part of the clinical follow-up.…”
Section: Emerging Issues In Twinsmentioning
confidence: 99%
“…Perinatal mortality of singletons is increased significantly after 42 weeks whereas perinatal mortality in twins starts to increase significantly after 37 weeks [19]. Prospective risk of fetal death in twin pregnancies, however, rises with advancing gestation, and it ranges between 0.2% and 0.4% per gestational week between 32 and 38 weeks' gestation [20]. Robinson et al [21] suggested that for women with uncomplicated monochorionic twins, the preferred timing of delivery is between 36 and 38 weeks' gestation to decrease fetal loss.…”
Section: Discussionmentioning
confidence: 99%
“…Birth weight discordance was calculated as the difference between birth weights divided by the birth weight of the larger twin [(larger birth weight − smaller birth weight)]/larger birth weight × 100%)] [9]. Degree of discordance was defined as median value of discordance in spontaneously conceived twins and those conceived by IVF.…”
Section: Methodsmentioning
confidence: 99%